2013
DOI: 10.4236/jbise.2013.69105
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vivo</i> relationship between the clinical epicondylar axis and the anterior pelvic plane in normal subjects

Abstract: Background: Several researchers consider the clinical epicondylar axis (CEA) as the functional flexion-extension axis of the knee. The anterior pelvic plane (APP) is commonly used as an anatomical reference plane of the pelvis. However, no study has investigated the relationship of the APP with the CEA and PCA. In this study, we aimed to investigate the relationship of the APP with the CEA and posterior condylar axis (PCA) in the standing and supine positions. Methods: We recruited 77 healthy Japanese subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…We previously described that CEA was approximately parallel to the transverse axis of the APP plane in the standing position in normal subjects [ 14 ] and in our current study, we reported that the KRA was almost 0° and that the tibia AP axis was approximately perpendicular to the CEA. This new concept in the current study may be important to integrate these two axes with regard to not only the anatomical reference, but also the kinesiology of the lower extremity including the pelvis, hip joint, and knee joint.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We previously described that CEA was approximately parallel to the transverse axis of the APP plane in the standing position in normal subjects [ 14 ] and in our current study, we reported that the KRA was almost 0° and that the tibia AP axis was approximately perpendicular to the CEA. This new concept in the current study may be important to integrate these two axes with regard to not only the anatomical reference, but also the kinesiology of the lower extremity including the pelvis, hip joint, and knee joint.…”
Section: Discussionsupporting
confidence: 70%
“…We previously reported that the CEA runs approximately parallel to the transverse axis of the anterior pelvic plane (APP) in the standing position in healthy subjects [ 14 ]. However, to our knowledge, no report has described the rotational alignment between APP and AP axis of the tibia, and if they are perpendicular to CEA in the standing position.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the foot and the extensor mechanism, such as the quadriceps femoris, must be maintained in the forward direction during walking. Imai et al [9] demonstrated that the anterior pelvic plane is parallel to the transepicondylar axis approximating the functional flexion axis of the knee in the standing position, which indicates that humans move with coinciding motion planes of the pelvis and knee joint. The vastus medialis, vastus lateralis, and vastus intermedius in the quadriceps femoris attach from the anterolateral aspect to the posterior linea aspera in the proximal femur [2].…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that the CEA and the transverse axis of the anterior pelvic plane (APP) are approximately parallel in the standing position in healthy subjects [ 14 ]. Moreover, we also described that the AP axis of the tibia is approximately perpendicular to the transverse axis of the APP in the standing position in healthy subjects [ 15 ].…”
Section: Introductionmentioning
confidence: 99%